PENGUKURAN KINERJA RANTAI PASOK UKM KALAMAI UNI WAR MENGGUNAKAN METODE SCOR DAN FUZZY AHP - Misnadesi Misnadesi; Misra Hartati (Universitas Ahmad Dahlan Indonesia, 2019)
UKM Kalamai Uni War is a SME produced food products kalamai. Problem faced in this SME is the delay of raw materials from supplier Therefore, this SME couldn’t fulfill demand from consumers. This SME also experienced delays for shipping products to consumers. Another problem is products returned from consumers because the products have expired. UKM Kalamai will suffer losses if this occurs continuously. This study aims to find out the indicators affected toward supply chain performance.of UKM Kalamai Uni War. SCOR and Fuzzy AHP are used to solve this problems. Based on the result, the performance achieved by Kalamai Uni War is 68, 68. This belongs to average or middle performance category. UKM Kalamai Uni War needs an improvement for better supply chain performance. The result of this study were obtained 22 key performance indicators (KPI) indicators and 14 proposed strategiesbased on mapping strategy.